2006
DOI: 10.1111/j.1463-6395.2006.00217.x
|View full text |Cite
|
Sign up to set email alerts
|

The ultrastructure of the spermatozoa of Boa constrictor occidentalis, with considerations on its mating system and sperm competition theories

Abstract: Tourmente, M., Cardozo, G., Bertona, M., Guidobaldi, A., Giojalas, L. and Chiaraviglio, M. The ultrastructure of the spermatozoa of Boa constrictor occidentalis , with considerations on its mating system and sperm competition theories. -Acta Zoologica (Stockholm) 87 : 25 -32 Sperm ultrastructure has been described for several families of Squamata in which it has been considered a valuable character source for phylogenetic studies. However, sperm competition and mating systems have been demonstrated to influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0
5

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 28 publications
0
20
0
5
Order By: Relevance
“…In addition, we described nine characters of the sperm tail (11,12,16,(20)(21)(22)(23)(24)(25) not recorded by those authors. Tourmente et al (2006) described the ultrastructure of the spermatozoa of Boa constrictor occidentalis, which diVers from Boa constrictor amarali in the shape of mitochondria in transverse section (circular in Boa constrictor occidentalis and irregular in Boa constrictor amarali). Further, Tourmente et al (2006) were not able to observe the epinuclear lucent zone, perforatorium, and perforatorium base plate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, we described nine characters of the sperm tail (11,12,16,(20)(21)(22)(23)(24)(25) not recorded by those authors. Tourmente et al (2006) described the ultrastructure of the spermatozoa of Boa constrictor occidentalis, which diVers from Boa constrictor amarali in the shape of mitochondria in transverse section (circular in Boa constrictor occidentalis and irregular in Boa constrictor amarali). Further, Tourmente et al (2006) were not able to observe the epinuclear lucent zone, perforatorium, and perforatorium base plate.…”
Section: Discussionmentioning
confidence: 99%
“…The monophyly of Boidae is well corroborated, but separate analyses conducted on morphological (Kluge 1991), molecular (Austin 2000), or a combination of both sets of characters (Burbrink 2005) lead to conXicting hypotheses of relationships among boids. A few ultrastructural studies on the sperm ultrastructure of boids include descriptions of the sperm tail (Austin 1965), neck and midpiece (Hamilton and Fawcett 1968) of Boa constrictor constrictor Linnaeus, 1758. Tourmente et al (2006 describe the spermatozoa of Boa constrictor occidentalis Philippi, 1873.…”
Section: Introductionmentioning
confidence: 99%
“…Some hypotheses have been suggested to explain their origins and functions, but none of them has been experimentally tested yet. Hamilton and Fawcett (1968) suggested that the multilaminar membranes could constitute a source of phospholipids to warrantee the motility of the gamete, and even recent works support this hypothesis (Tourmente et al, 2006). The elevated amount of mitochondria stored in an unusual elongated midpiece would indicate high levels of energy production, which would explain the necessity of providing an extra source of energy to sustain these metabolic capacities (Oliver et al, 1996 andTourmente et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, ultrastructural descriptions of the spermatozoon in species of snakes are restricted to a few works, including: Austin (1965), Hamilton and Fawcett (1968), Furieri (1970), Jamieson and Koehler (1994), Jamieson (1995), Harding et al (1995), Oliver et al (1996), Tourmente et al (2006), Tavares-Bastos et al (2007). On the other hand, the knowledge concerning the relevance of structural aspects of the gamete to guarantee the fertilization success is still limited.…”
Section: Introductionmentioning
confidence: 99%
“…Sperm ultrastructure has been described for several species of Squamata (Giugliano et al 2002;Jamieson 1999;Oliver et al 1996;Tavares-Bastos et al 2002;Teixeira et al 1999aTeixeira et al , b, 2002Ferreira and Dolder 2003;Vieira et al 2004) and several attempts have been made to use sperm ultrastructure for phylogeny inference in the serpent taxa Colubridae, Pythonidae, Elapidae (Jamieson and Koehler 1994;Oliver et al 1996), Viperidae (Al-Dokhi 2004), Typhlopidae (Harding et al 1995), and recently Boidae (Tavares-Bastos et al 2008). Tourmente et al (2006) described the spermatozoa of Boa constrictor occidentalis (Philippi, 1873) and proposed some ultrastructural traits as adaptations to increase motility and/or longevity under sperm competition and storage conditions. Since these features are thought to be widespread among the Serpentes in general (Olsson and Madsen 1998;Shine 2003), and Crotalinae in particular (Schuett 1992;Duvall et al 1992), similar spermatozoal characteristics would be expected.…”
Section: Introductionmentioning
confidence: 97%